Heavy Metals in Fertilizers in Soils Due to Continous Fertilizer Use - Sathyaprakasan S (Department of Soil Science & Agricultural Chemistry, College of Agriculture, 1989)
The possible heavy metal pollution through continuous use of chemical fertilizers for the last several years, has become a topic of grave concern in recent times. It is possible that such heavy metals if present in soil in sufficient quantities, may enter the food chain and endanger animal and human life. The present study was taken up with a view to establishing whether the accumulation of heavy metals in soils and plants is appreciable so as to pose any health hazards. With a view to achieve the above aim soils and rice plants grown in four major rice soils of Kerala which were receiving high doses of fertilizers for the last several years, and also eight common fertilizers used in these areas were collected and analysed for the heavy metal content with emphasis to cadmium. Soils from plots receiving organic manures, chemical fertilizers and a combination of both from one permanent manorial experiment with tall’ , india rice (25 years under same treatments) and soil, plant and grain from another permanent manorial experiment with dwarf Jeponica rice (13 years old) were collected and analysed for their heavy metal content. A pot culture with added cadmium alongwith fertilizers as per package of practices was also conducted incorporating rice, amaranthus and guinea grass to study the plant to plant variation in the uptake and accumulation of heavy metals in their tissues. The result of the studies showed that the phosphatic fertilizers contained the highest amount of heavy metals and among the phosphatic fertilizers maximum amount of Cd was found in factomphos while Ni and Pb were highest in mussoorie rock phosphate. Among the four soil types investigated viz. the Karappadam, Kayal, Kari and Trivandrum sandy loam the highest content of total Cd Ni and Pb were observed in Karappadam, Kayal and Kari soils respectively. The content of extractable Cd and Pb was highest in Kari soil while the extractable Ni was highest in Kayal soil. The mean Cd and Ni content of rice straw from karappadam soil was found to be the highest where as the rice straw from Kayal soil registered the maximum content of Pb. The results obtained from the Permanent Menurial Experimental trials revealed that the continuous use of organic matter alone or organic matter and chemical fertilizers in combination increased the heavy metal content in soils and plants. In the pot culture experiment with rice there was no significant variation in the total as well as the extractable Cd in the soil after harvest among treatments with 0, 10, 20 and 30 g Cd ha-1. The same trend was observed in the straw and grain as well. The Cd content in amaranthus also was not having significant variation among treatments. But in guinea grass the Cd content was significantly higher in the pot which received the highest dose of Cd viz. 30 g/ha. Since the doses viz. 10, 20 and 30g Cd per heactre were fixed on the basis of annual addition through fertilizers the impact could be much less and therefore the results presently obtained cannot be’,said to be conclusive. Correlation studies revealed that the soil total Cd was positively and significantly correlated to plant Cd content. The extractable Cd was also positively and significantly correlated to soil P. Applied N and P fertilizers were seen to significantly influence plant Cd content. The applied K fertilizers on the other hand were seen to positively enhance plant Cd, Ni and Pb contents.